Sequence and properties of pentaerythritol tetranitrate reductase from Enterobacter cloacae PB2. - French, C E (1996)
Pentaerythritol tetranitrate reductase, which reductively liberates nitrite from nitrate esters, is related to old yellow enzyme. Pentaerythritol tetranitrate reductase follows a ping-pong mechanism with competitive substrate inhibition by NADPH, is strongly inhibited by steroids, and is capable of reducing the unsaturated bond of 2-cyclohexen-1-one.